Building A Strong Culture And Improving Performance: Organizational Strategies For Developing Superior Human Resources - Brigida Endah Nuraeni; Edi Sumarya; Agus Sekti Susila Atmaja (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to understand the role of organizational culture in improving employee performance at Sekolah Tinggi Ilmu Ekonomi Bentara Persada (STIE BP) Batam. A qualitative approach was employed, using triangulation techniques to validate data through interviews and direct observations. The findings reveal that the organizational culture established at STIE BP characterized by values such as honesty, responsibility, care, fairness, and consistency has been internalized by employees and serves as a guiding principle in carrying out their duties and responsibilities. This culture is reflected in routine activities such as staff recollections, the use of symbols and uniforms, as well as the implementation of the institution’s motto and vision-mission. In addition, the quality assurance system and the application of Key Performance Indicators (KPIs) contribute to increased productivity and work motivation. The findings also indicate that organizational culture fosters a sense of belonging, enhances self-confidence, and strengthens employee engagement with the institution. Thus, a strong organizational culture not only functions as a tool for social control but also serves as a key driver of employee performance.